Sociodemographic Determinants of Women’s Empowerment During Pregnancy: A Cross-sectional Study in Indonesia - Erni Dwi Widyana; Siti Nor Ismalina Isa; Siti Khuzaimah Ahmad Sharoni; Suryanto Suryanto (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: Women’s empowerment related to pregnancy plays an important role in enhancing maternal and infant health, during pregnancy, childbirth and the postpartum period. However, the determinants of women’s empowerment in the context of pregnancy are still not fully understood, particularly in middle-income countries. This study aimed to determine the level of women’s empowerment related to pregnancy and identify its associations with sociodemographic characteristics. Methods: This study used a cross-sectional design involving pregnant women who underwent antenatal care at various health facilities in Malang, Indonesia. The Pregnancy Empowerment Scale (PRES) questionnaire has been used to measure the level of empowerment of women to control their health during pregnancy, which consists of four subscales: Provider Connectedness, Skillful Decision-Making, Peer Connectedness, and Getting Voice. This questionnaire has been distributed to 413 pregnant women. Sociodemographic characteristics assessed included age, gestational age, parity, pregnancy risk factors, household income, and average distance to antenatal care centers. The data were analysed using multiple linear regression analysis to determine the relationship between the factors and the level of empowerment. Results: The results of this study indicate that the majority (95.6%) of pregnant women have high women’s empowerment, while the average distance from the antenatal care centre is the only significant and positive sociodemographic factor influencing women’s empowerment related to pregnancy. However, the overall contribution of sociodemographic variables to this empowerment is relatively small. The regression model shows R² = 0.041, allowing for unmeasured psychosocial or cultural factors that could play a role. Conclusion: Sociodemographic factors play an important role in women’s empowerment related to pregnancy. To enhance empowerment, community-based approaches that consider access to health services and improvement of family economic welfare should be considered.